PENGEMBANGAN PROTOTIPE PROGRAM INTERPRETASI ELEKTROKARDIOGRAM (PIE) MENGGUNAKAN SISTEM PAKAR - (NIM : 23399002), ndurrochman
Abstract : Electrocardiography is a general simple, useful, practical diagnostic test. It helps to observe the heart condition. The electrocardiogram (ECG) must always be interpreted in the light of the entire clinical picture; moreover, it should never be the sole basis for judging the cardiac status. In the other hand, the man who knows how to interpret the ECGs is lack in resources. This thesis describes The Development of Expert System Prototype of the Electrocardiogram Interpretation Program (PIE) as the tools that could assist young physicians to study how to interpret ECGs. The sources of the expert domain of the prototype come from ECG textbooks. Object oriented program (OOP) was used to develop the PIE prototype, where the inference engine and knowledge base of the prototype could be separated, because the encapsulation in OOP could separate different objects. The advantage of this OOP expert system is in next development of prototype, either the intelligence or the working characteristic (online with EKG recorder). The ECGs parameters fed into the prototype descriptively. The OOP expert system enable to interpret all of the common variations of the ECGs (17 of 21), but it disable to interpret correctly the unique and complicated variations of the ECGs (4 of 21). These errors come from the source of the knowledge base that was ECG textbooks, which contain only the basic variations of ECGs.